2010
DOI: 10.7196/samj.3865
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite: Admissions at a tertiary health care centre in Maharashtra, India

Abstract: Snakes are found all over the world except in the Arctic, New Zealand and Ireland, and are more commonly distributed in temperate and tropical countries.1 Snakes are most likely to bite human beings when they feel threatened, startled or provoked, and/or have no means of escape when cornered. Snakes are likely to approach residential areas when attracted by prey, such as mice and frogs. The Deccan plateau, with its agricultural land and hot, dry climate, provides an ideal environment for cobras, kraits and vip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 4 publications
10
29
1
Order By: Relevance
“…The predominance of male victims suggests a special risk of outdoor activity. This is comparable to the studies done by other authors [4,[11][12][13][14].…”
Section: Sex and Educationsupporting
confidence: 82%
See 1 more Smart Citation
“…The predominance of male victims suggests a special risk of outdoor activity. This is comparable to the studies done by other authors [4,[11][12][13][14].…”
Section: Sex and Educationsupporting
confidence: 82%
“…Rural inhabitants form the biggest chunk of casualties (67.5%) attributed to the labour they are generally engaged in and this collaborates with inference drawn from other studies [4,[9][10][11][12][13].…”
Section: Rural Areasupporting
confidence: 68%
“…16,19 It was encouraging to know that in the present study 364 (91%) of the participants did not consider going to a faith healer or quack as a treatment option after snake bite, this finding was similar to the study done by Pandey et al 4 While in other similar studies 86% of snakebite victims in Bangladesh, 75% in Pakistan, and 61% in Maharashtra, India still visit traditional healers. [20][21][22] In the present study it was found that 305 (76.25%) of the total participants offer milk to snakes brought by local Snake charmers on Nag Panchami festival which proves detrimental to the snake's health. Therefore awareness camps in laying emphasis on imparting basic knowledge about snake identification, snakebite prevention and clearing misconceptions should be held in schools, proper first aid methods for snakebites should be demonstrated through various outreach activities and increased awareness about snake and snakebite identification among heath care workers and general population should also be done.…”
Section: Discussionmentioning
confidence: 99%
“…Inamdar et al [17] from Central India studied the outcome, seasonal variation, and death pattern of snakebite cases over 10 years. They concluded snake bite as a life-threatening emergency; early appropriate use of antivenom and close monitoring will reduce complications and mortality.…”
Section: Discussionmentioning
confidence: 99%